2020
DOI: 10.1080/25785826.2020.1796285
|View full text |Cite
|
Sign up to set email alerts
|

Anti-DNA antibodies cross-reactive with β2-glycoprotein I induce monocyte tissue factor through the TLR9 pathway

Abstract: Antibodies specific for cardiolipin (CL)-b 2-glycoprotein I (b 2 GPI) are known to induce tissue factor (TF) expression by monocytes and endothelial cells which leads to a prothrombotic state in antiphospholipid syndrome (APS), but the mechanism is not fully elucidated. Previously, we reported that the mouse monoclonal anti-CL-b 2 GPI antibody WB-6 crossreacts with DNA, enters monocytes via binding to cell surface DNA, and induces TF expression. The current study aimed to identify the intracellular signaling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Additional studies demonstrated that aPL may also induce the translocation of TLR-7 or TLR-8 from the endoplasmic reticulum to the endosome [93], these effects depend on the uptake of aPL into the endosome, subsequent activation of endosomal NADPH oxidase and generation of superoxide. A pivotal role for TLR-9 pathway in TF production by monocytes was also recently reported [94].…”
Section: Signal Transduction Pathways Triggered By Aplmentioning
confidence: 65%
“…Additional studies demonstrated that aPL may also induce the translocation of TLR-7 or TLR-8 from the endoplasmic reticulum to the endosome [93], these effects depend on the uptake of aPL into the endosome, subsequent activation of endosomal NADPH oxidase and generation of superoxide. A pivotal role for TLR-9 pathway in TF production by monocytes was also recently reported [94].…”
Section: Signal Transduction Pathways Triggered By Aplmentioning
confidence: 65%
“…Finally, ROS production by endosomal NOX-2 may be blocked with ubiquinol or patients with non-APS related thrombosis [36,37]. Purified patient anti-β2GPI IgG increases the TF expression in healthy donor monocytes [38,39]. Macrophages from anti-β2GPI antibody-treated mice also produce significantly more TF mRNA [30].…”
Section: Procoagulant Effects Of Apl On Monocytesmentioning
confidence: 99%
“…A study of how WB-6 (a mouse monoclonal anti-β2Gpi antibody) contacts and activates resting-state monocytes showed that monocytes internalizing WB-6 express TF and TNF-α, TNFα stimulates ECs to express ICAM-1 and VCAM-1 (181). Later, another study identified the signaling pathways within cells involved in this process and suggested that the induction of TF expression was the result of the internalization of DNA-activated TLR9 together with cross-reactive antibodies produced by SLE secondary APS (182). It has proved that the β2GPI dimerization domain V(β2GPI-dV) dimerization of β2GPI-dV is sufficient to induce the up-regulation of procoagulant activity of monocytes (183).…”
Section: Antiphospholipid Syndrome (Aps)mentioning
confidence: 99%